Socialization of The Teaching Games for Understanding Learning Model to School Physical Education Teacher Upper Middle School in Kupang City - Michael J.H Louk; Lukas Maria Boleng; Veramyta M.M. Flora Babang; Al Ihzan Tajuddin; Ronald Dwi Ardian Fufu; Jurdan Marthin Siahaan; Salmon Runesi; Maria Andriani Barek Ladjar (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Learning physical education has a different approach from other subjects. This is due to the emphasis on the development of psychomotor aspects rather than cognitive and affective aspects. In fact, the process of learning physical education emphasizes not only psychomotor aspects but also cognitive and affective aspects simultaneously, as internationally standardized by ICHPER-SD and UNESCO that physical education and sports in schools must describe the discipline of knowledge, skills and behavior covering the domains psychomotor, cognitive, and affective. This demand results in the need for a learning approach that can involve and develop all aspects of education.The Tactics Learning Approach (TGfU) pays very broad attention to the cognitive and psychomotor domains. For example, the cognitive domain is obtained from exams in high and secondary schools. Behavioral measurement is carried out to measure the effectiveness and involvement of the game that was developed to contribute to the measurement of actions and skills that are measured in relation to the cognitive domain. Very little attention has been paid to researchers and educators in the cognitive and affective domains. The influence of work and pleasure in sports will give greater influence through game learning. For example, children, coaches and parents all need to know that games and game situations are more enjoyable than continuous, technique-oriented practice.